Reframing the narrative: Black maternal mental health and culturally meaningful support for wellness. Issue 4 (20th January 2021) - Parker, Amittia
ABSTRACT: Black mothers with young children have encountered pernicious, multidetermined, racial disparities in the United States for centuries. However, disorders, risks, and stressors among Black mothers with young children are presented in the extant literature with little attention to their strengths, supports, or culturally appropriate ways to intervene and this furthers racism and White supremacy. Further, incomplete and negative narratives about Black mothers are perpetuated. Therefore, this article uses the Afrocentric perspective to better understand the state of Black maternal mental health and supports for mental health. Culturally centered recommendations are presented to move the field of infant mental health toward racial justice‐oriented practice, policy, and research. RESUMEN: Las madres negras con niños pequeños han enfrentado disparidades raciales perniciosas y de múltiples determinantes en los Estados Unidos por siglos. Sin embargo, los trastornos, riesgos y factores de estrés entre las madres negras con niños pequeños se presentan dentro de la existente información y estudios impresos con poca atención a sus puntos fuertes, los apoyos o las apropiadas maneras culturales para intervenir, lo cual fomenta el racismo y la supremacía blanca. Es más, se perpetúan las narrativas incompletas y negativas acerca de las madres negras. Por tanto, este artículo usa la perspectiva afro‐céntrica para comprender mejor la situación de la salud mental entre madres negras y los apoyos a la salud mental. Se presentan recomendaciones centradas en lo cultural para acercar el campo de la salud mental infantil hacia la práctica orientada a la justicia racial, las políticas y la investigación. RÉSUMÉ: Black mothers with young children have encountered pernicious, multi‐determined, racial disparities in the U.S. for centuries. However, disorders, risks, and stressors among Black mothers with young children are presented in the extant literature with little attention to their strengths, supports, or culturally appropriate ways to intervene and this furthers racism and white supremacy. Further, incomplete and negative narratives about Black mothers are perpetuated. Therefore, this article uses the Afrocentric perspective to better understand the state of Black maternal mental health and supports for mental health. Culturally centered recommendations are presented to move the field of infant mental health towards racial justice oriented practice, policy, and research. ZUSAMMENFASSUNG: Umformulierung eines Narrativs: Die psychische Gesundheit schwarzer Mütter und kulturell bedeutsame Unterstützung für das Wohlbefinden Schwarze Mütter mit kleinen Kindern sind in den USA seit Jahrhunderten verhängnisvollen, multideterminierten, rassistischen Ungleichheiten ausgesetzt. In der vorhandenen Literatur werden Störungen, Risiken und Stressfaktoren bei schwarzen Müttern mit kleinen Kindern dargestellt, wohingegen ihre Stärken, Stützen oder kulturell angemessene Interventionsmöglichkeiten kaum berücksichtigt werden. Dies fördert Rassismus und die weiße Vormachtstellung (white supremacy). Außerdem werden unvollständige und negative Narrative über schwarze Mütter aufrechterhalten. Um den Zustand der psychischen Gesundheit schwarzer Mütter besser zu verstehen und zu unterstützen, verwendet dieser Artikel die afrozentrische Perspektive. Empfehlungen mit kulturellem Fokus sollen für den Bereich der psychischen Gesundheit von Säuglingen eine auf ethnische Gerechtigkeit ausgerichtete Praxis, Politik und Forschung vorgeben. 抄録: 視点を変えて物語を見る:黒人の母親の精神保健と文化的に真に意義あるウェル ネスへの支援 アメリカでは何世紀にも渡り、幼児を持つ黒人の母親は、悪質で様々な決定要因を持つ不当な人種差別に直面してきた。しかし、幼児を持つ黒人の母親の疾患やリスク、ストレス要因について既存の文献に紹介されてはいても、その強さやそれに対する支援、あるいは文化的に適切な介入方法についてはほとんど触れられていないことが、人種差別と白人至上主義をさらに促進している。さらに、黒人の母親にまつわる不完全な否定的物語が永遠に語り継がれている。そこで、この論文は黒人の母親の精神保健と精神保健への支援の実態をよく理解するために、黒人文化主義的展望を活用する。乳幼児精神保健の領域を人種的正義指向の実践、政策、研究へと移行するために、文化至上の推奨事項が提示される。 摘要: 几个世纪以来, 在美国, 有着年幼子女的黑人母亲遭遇了恶性的、多元判定的种族不平等。然而, 现有的文献描述了携带年幼子女黑人母亲的疾病、风险和压力源, 但很少关注她们的长处、给予支持或文化上适当的干预方式, 这进一步加剧了种族主义和白人至上主义。此外, 关于黑人母亲片面的、消极的叙述被延续了下来。因此, 本文运用以非洲为中心的视角来更好地了解黑人产妇的心理健康状况, 并为其心理健康提供支持。文章提出了以文化为中心的建议, 以期推动婴儿心理健康领域朝着以种族公正为导向的实践、政策和研究方向发展。 ملخص: إعادة صياغة المشهد: الصحة النفسية للأمهات السود والدعم الهادف ثقافياً طالما تعرضت الأمهات السود اللواتي لديهن أطفال صغار لأشكال مختلفة من التفرقة العرقية الخبيثة في الولايات المتحدة لعدة قرون. ومع ذلك ، يتم تناول الاضطرابات والمخاطر والضغوطات بين الأمهات السود مع الأطفال الصغار في الأبحاث بدون إعطاء اهتمام كافي لنقاط القوة لديهم ، والدعم ، أو الطرق المناسبة ثقافيا للتدخل وهذا يعزز العنصرية ونظرية استعلاء البيض. وعلاوة على ذلك، يتم تكرار الروايات غير المكتملة والسلبية حول الأمهات السود. لذلك، تستخدم هذه المقالة المنظور الأفروسنتي للوصول إلى أفضل لحالة الصحة النفسية للأمهات السود ووسائل الدعم لصحتهم النفسية. وتقدم الدراسة توصيات تركز على الثقافة من أجل نقل مجال صحة الرضع النفسية نحو الممارسة والسياسات والبحوث ذات التوجه نحو العدالة العرقية.